Due To Legal Determination Of Religious Courts Demak Decision No. 09 / PDT.P / 2018 / PA DMK About Adoption Realization - Rodiyah Rodiyah; Akhmad Khisni (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Society has long recognized the legal institution of adoption even before the time of the Prophet society has implemented a system of adoption with the motivation or a different purpose, among others, to continue the descent, carry on business and so on. In Indonesian society not many people know about the implementation process since the adoption in court litigation adoption petition, the case investigation in the trial until the stage of determination of the judge. This study uses the approach of law (statute aproach) and approach to the case. Law approach is used to determine the overall legal regulations, especially laws governing adoption in Indonesia. Case approach aims to study the application of norms or rules of law in the determination of adoption. The results of this thesis research in the Stipulation No. 09 / Pdt.P / 2018 / PA.Dmk is the implementation of adoptions carried out aimed at the best interests of children in the welfare and protection of children and the application of law by the judge in legal considerations. As a result of the law of the designation is the association adopted child with the adoptive parents only form of legal relationship in the form of transfer of responsibility of the biological parents and not result in legal consequences inherit each other between himself and his adoptive parents are not entitled to inherit each other to each other, but the adopted child can accept the will, and vice versa.Keywords: Because of Law; Kids Appointment; Religious Courts.